THE ESSENCE AND TYPES OF INFORMATION SECURITY ENTERPRISES - Русин-Гриник, Роман; Гриновець, Маркіян; Борсук, Олег; Фтемов, Едуард; Круглов, Сергій (SWorldJournal, 2023)
The article proves that the formation and development of information support of enterprises is influenced by the managerial needs of managers, their professionalism and motivation. It is argued that under the influence of the mentioned factors, the proce